Pemberdayaan Masyarakat Lanjut Usia melalui Perilaku Hidup Bersih dan Sehat selama Pandemi Covid-19 - Nurman Achmad (PERSPEKTIF, 2022)
Covid-19 or SARS-CoV-2 is a virus that emerged at the end of 2019 and has never been identified in the human body before. According to the World Health Organization (WHO), this virus is vulnerable to attack the elderly who have high mortality and morbidity in the face of the Covid-19 pandemic. In this case, of course, the elderly really need access to intense health services, especially for the elderly who have a history of chronic or degenerative diseases. One of the efforts that can be done is such as maintaining cleanliness through Clean and Healthy Living Behavior. Serdang Bedagai is one of the regencies that are included in the ten regencies that have the largest elderly population in North Sumatra. Therefore, it is necessary to optimize empowerment in these districts to improve the quality of life of the elderly during the Covid-19 pandemic. The implementation method in this empowerment activity is through lectures and practice, followed by gymnastics. With this activity, the participants understood how to maintain cleanliness and health and began to implement physical activity in an effort to improve health.